Method for improving recovery rate of titanium dioxide

By mixing the industrial deactivated denitrification catalyst with an alkaline solution, converting it into titanate, and adjusting it through organic acid solution and flocculant, the problem of low titanium dioxide recovery in the prior art is solved, and the recovery of titanium dioxide with high purity and small particle size is achieved, which is suitable for the preparation of light, electrocatalysts and denitrification catalysts.

CN119503872APending Publication Date: 2025-02-25QUZHOU INSTITUTE FOR INNOVATION IN RESOURCE CHEMICAL ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669577.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing process for recycling titanium dioxide is low, resulting in low resource utilization.

Method used

By mixing the industrial deactivated denitrification catalyst with an alkaline solution, converting it into titanate, then adjusting it through organic acid solution, adding a flocculant for nucleation and crystallization, and finally obtaining high-purity and small particle size titanium dioxide through calcination.

Benefits of technology

The recovery rate of titanium dioxide is achieved by being greater than 98%, the particle size distribution is narrow, the total surface acid amount meets the requirements of the catalyst, the purity is greater than 99.2%, and pollution and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503872A_ABST
    Figure CN119503872A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the recovery rate of titanium dioxide, belongs to the technical field of resource recovery and utilization, and solves the problem of low resource utilization rate caused by low recovery rate of the existing titanium dioxide recovery process. The method comprises the following steps: efficiently leaching W and V: mixing an industrial inactivated denitration catalyst with an alkaline solution, reacting, and removing supernate to obtain a solid; converting titanium dioxide into titanate: mixing the obtained solid with an alkaline solution, and reacting to obtain filter residues; converting the titanate into titanium dioxide: adding an organic acid solution into the obtained filter residue to obtain a solid-liquid mixture, transferring the solid-liquid mixture into a reactor for nucleation to obtain slurry, adding a flocculating agent into the slurry, crystallizing to obtain turbid liquid, separating, and roasting to obtain TiO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recycling, and in particular to a method for improving the recovery rate of titanium dioxide. Background Art

[0002] Titanium dioxide has a wide range of uses, covering batteries, electronic components, catalysts and other fields. In the battery industry, titanium dioxide's high ionic conductivity and chemical stability make it a candidate material for high-performance batteries; in the field of optical and electronic device research and development, titanium dioxide is used to prepare optical devices and electronic components due to its special structure and optical properties; in the field of catalysts, titanium dioxide's high specific surface area and chemical stability make it have great potential in catalyst design and reaction control, and can be used as a catalyst or catalyst carrier.

[0003] The existing process for recycling titanium dioxide has a low recovery rate, resulting in low resource utilization. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a method for improving the recovery rate of titanium dioxide, so as to solve the problem that the recovery rate of existing titanium dioxide recovery processes is low, resulting in low resource utilization.

[0005] The purpose of the present invention is mainly achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for improving the recovery rate of titanium dioxide, comprising the following steps:

[0007] Efficient leaching of W and V: Mix the industrial deactivated denitrification catalyst with an alkaline solution, react, remove the supernatant, and obtain a solid;

[0008] Titanium dioxide is converted into titanate: the obtained solid is mixed with an alkaline solution, reacted, and a filter residue is obtained;

[0009] Titanate is converted into titanium dioxide: an organic acid solution is added to the obtained filter residue to obtain a solid-liquid mixture, the solid-liquid mixture is transferred into a reactor for nucleation to obtain a slurry, a flocculant is added to the slurry for crystallization to obtain a suspension, and the suspension is separated and calcined to obtain TiO2.

[0010] Optionally, the flocculant includes one or more of starch, cellulose and chitosan.

[0011] Optionally, the mass of the flocculant accounts for 0.01%-0.05% of the mass of the slurry.

[0012] Optionally, the organic acid solution is a mixed acid of one or more of tartaric acid, citric acid, lauric acid and oxalic acid.

[0013] Optionally, the concentration of the organic acid solution is 0.5-2 mol / L.

[0014] Optionally, the crystallization temperature is 90-100° C., and the crystallization time is 2-5 h.

[0015] Optionally, the calcination temperature is 500-900° C. and the calcination time is 4-6 hours.

[0016] Optionally, calcination is performed in a muffle furnace.

[0017] Optionally, the recovery rate of TiO2 is greater than 98%.

[0018] In a second aspect, the present invention further provides a titanium dioxide recovered by the above method, wherein the titanium dioxide has a small particle size, the most probable particle size is 18.6-19.3 nm; the particle size distribution is narrow, the D(30) particle size is less than 30 nm, the D(50) particle size is less than 40 nm, and the D(90) particle size is less than 50 nm; the total surface acid content is not less than 4.68×10 -4 mol / g; purity>99.2%.

[0019] In a third aspect, the present invention also provides an application of the above-mentioned titanium dioxide in the preparation of photocatalysts, electrocatalysts and denitrification catalysts.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] (1) The present invention adds a flocculant during the nucleation process to precipitate small particles in the solid-liquid mixture, so that the fine titanium dioxide particles can be crystallized and grown, and can be separated from the reaction system, thereby improving the recovery rate of titanium dioxide. Specifically, the recovery rate of titanium dioxide in the deactivated denitration catalyst of the present invention is greater than 98%.

[0022] (2) The present invention adds an organic acid solution during the conversion of titanate into titanium dioxide. On the one hand, the particle size distribution of the titanium dioxide finally recovered is regulated, so that the particle size distribution of the titanium dioxide is narrower, and the particle size distribution of the recovered titanium dioxide is very narrow by controlling the amount of organic acid solution added. Specifically, the D(30) particle size of the recovered titanium dioxide is below 30 nm, the D(50) particle size is below 40 nm, and the D(90) particle size is below 50 nm. On the other hand, the use of organic acid is conducive to controlling the total surface acid content of the product, so that the total surface acid content of the recovered titanium dioxide is not less than 4.68×10 -4 mol / g, which meets the requirements of photocatalyst and denitration catalyst for the total acid content of titanium dioxide. In addition, compared with the prior art using inorganic strong acid, the present invention uses organic weak acid, which can greatly reduce pollution and energy consumption.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can be obvious from the description or understood by practicing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0025] Figure 1 The X-ray diffraction pattern of the sample obtained in Example 1 of the present invention;

[0026] FIG2( a) is a scanning electron microscope photograph of the sample obtained in Example 1 of the present invention;

[0027] FIG2( b) is a scanning electron microscope photograph of the sample obtained in Comparative Example 5 of the present invention;

[0028] FIG3( a ) is a particle size distribution diagram of the sample in FIG2( a );

[0029] Figure 3(b) is the particle size distribution diagram of the sample in Figure 2(b). DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0031] The present invention uses industrial deactivated denitration catalyst as raw material to prepare titanium dioxide with high purity, small particle size and complete and regulated organizational structure, and prepares titanium dioxide-based industrial catalyst based on this.

[0032] In a first aspect, the present invention provides a method for improving the recovery rate of titanium dioxide, which uses an industrial deactivated denitration catalyst as a raw material to prepare and synthesize titanium dioxide with high purity, small particle size, and complete and regulated organizational structure.

[0033] Specifically, the recovery method of the present invention comprises the following steps:

[0034] Efficient leaching of W and V: pre-treating the industrial deactivated denitration catalyst and mixing it with an alkaline solution to obtain a mixed solution, reacting it, removing the supernatant, and obtaining a solid;

[0035] Titanium dioxide is converted into titanate: the solid obtained in the above step is mixed with the first alkaline solution to obtain a second suspension, the second suspension is transferred into a micro-liquid membrane reactor, back-mixed, transferred into a reactor for reaction, centrifuged, and a filter residue is obtained;

[0036] Titanate is converted into titanium dioxide: an organic acid solution is added to the filter residue obtained in the previous step to obtain a solid-liquid mixture, the solid-liquid mixture is transferred into a micro-liquid membrane reactor for nucleation to obtain a slurry, a flocculant is added to the slurry, crystallization is performed to obtain a suspension, centrifugation, washing, drying and calcination are performed to obtain TiO2.

[0037] In the present invention, firstly, efficient leaching of W and V in the deactivated denitration catalyst is achieved, and part of the titanium dioxide in the deactivated denitration catalyst is converted into titanate. Then, the titanium in the deactivated denitration catalyst that has not been converted into titanate is converted into titanate. Secondly, the titanate is converted into titanium dioxide, and other impurities such as Ca, Fe, Al, etc. contained in the deactivated denitration catalyst are removed.

[0038] Specifically, after the industrial deactivated denitration catalyst is mixed with the alkaline solution to obtain a mixed solution and before the reaction, the method further includes step 1-1: adding a dispersant to the mixed solution to obtain a first suspension, transferring the first suspension into a micro-liquid membrane reactor, back-mixing, and centrifuging.

[0039] Specifically, the liquid-to-solid ratio in the mixed solution is (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1.

[0040] The purpose of adding a dispersant in step 1-1 is to make the solid-liquid contact better, thereby shortening the back-mixing time (i.e., the time for the vanadium and tungsten components in the deactivated denitration catalyst to separate from the titanium component), thereby improving the recovery timeliness. The dispersant is acrylate, polyurethane, polyacrylamide, polyvinyl alcohol or polyethylene glycol. The volume of the dispersant accounts for 1‰-5‰ of the volume of the first suspension, for example, 1‰, 2‰, 3‰, 4‰, 5‰.

[0041] Specifically, in step 1-1, the back-mixing time is 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min. The back-mixing temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C.

[0042] In step 1-1, during back mixing, the slit of the micro liquid membrane reactor is 0.1-0.5 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm.

[0043] Specifically, in the mixed solution obtained by mixing the industrial deactivated denitration catalyst with the alkaline solution, the alkaline solution is a first alkaline solution. The first alkaline solution is a NaOH solution, a KOH solution, a sodium bicarbonate solution or a sodium carbonate solution, and its mass concentration is 5wt%-10wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%.

[0044] Specifically, when titanium dioxide is converted into titanate, the liquid-to-solid ratio of the second suspension is (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1.

[0045] The alkaline solution in which titanium dioxide is converted into titanate is a second alkaline solution, and the second alkaline solution is a NaOH solution, a KOH solution, a sodium bicarbonate solution or a sodium carbonate solution, and its mass concentration is greater than the mass concentration of the first alkaline solution. Specifically, the mass concentration of the second alkaline solution is 20-40wt%, for example, 20wt%, 22wt%, 24wt%, 25wt%, 27wt%, 28wt%, 30wt%, 35wt%, 40wt%, etc.

[0046] It should be noted that the purpose of adding alkaline solution to the efficient leaching of W and V in the present invention is: first, to efficiently leach W and V in the deactivated denitration catalyst; second, to convert part of the titanium dioxide in the deactivated denitration catalyst into titanate. The purpose of adding alkaline solution to the conversion of titanium dioxide into titanate is to convert the titanium in the deactivated denitration catalyst that has not been converted into titanate into titanate.

[0047] The present invention adopts two steps to add alkaline solution, and by controlling the mass concentration of the second alkaline solution to be greater than the mass concentration of the first alkaline solution, the above-mentioned purpose can be achieved, and the reaction is more complete as a whole, which is conducive to removing metals such as V and W, thereby improving the purity of titanium dioxide. And by selecting the mass concentration of the first alkaline solution to be 5-10wt% and the mass concentration of the second alkaline solution to be 20-40wt%, the degree of reaction is further improved, thereby improving the purity of titanium dioxide. Specifically, the purity of titanium dioxide recovered by the present invention is>99.2%.

[0048] Specifically, when titanium dioxide is converted into titanate, the back-mixing time is 1-10 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes. The back-mixing temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C.

[0049] When titanium dioxide is converted into titanate, the slit of the micro-liquid membrane reactor during back mixing is 0.1-0.5 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm.

[0050] In converting titanium dioxide into titanate, the reaction temperature in the reactor is 120-150°C, for example, 120°C, 130°C, 140°C, 150°C.

[0051] The reaction pressure is 0.3-2 MPa, for example, 0.3 MPa, 0.5 MPa, 0.8 MPa, 1 MPa, 1.3 MPa, 1.5 MPa, 0.7 MPa, 1.8 MPa, 2 MPa.

[0052] The reaction time is 2-5 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h.

[0053] Specifically, when titanate is converted into titanium dioxide, the role of adding an organic acid solution is to regulate the particle size distribution of the titanium dioxide finally recovered, or more precisely, to make the particle size distribution of the titanium dioxide narrower. The present invention makes the particle size distribution of the recovered titanium dioxide very narrow by adding an organic acid solution and controlling the amount of the organic acid solution added. Specifically, the D(30) particle size of the recovered titanium dioxide is below 30nm, the D(50) particle size is below 40nm, and the D(90) particle size is below 50nm. Exemplarily, the concentration of the organic acid solution is 0.5-2mol / L, for example, 0.5mol / L, 0.7mol / L, 0.5mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 2mol / L.

[0054] In the conversion of titanate to titanium dioxide, the mass volume concentration of the solid-liquid mixture is 0.1-0.5 g / mL, for example, 0.1 g / mL, 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, 0.5 g / mL.

[0055] The organic acid is one or more mixed acids selected from tartaric acid, citric acid, lauric acid and oxalic acid. The flocculant is one or more selected from starch, cellulose and chitosan.

[0056] In the conversion of titanate to titanium dioxide, the slit of the micro-liquid membrane reactor is 0.1-0.5 mm, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm. The nucleation temperature is 50-100° C., for example, 50° C., 60° C., 70° C., 80° C., 90° C., 100° C. The nucleation time is 1-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min.

[0057] In the conversion of titanate to titanium dioxide, the role of adding a flocculant is to precipitate small particles in the solid-liquid mixture, so that the fine titanium dioxide particles can be crystallized and grown, and can be separated from the reaction system, thereby improving the recovery rate of titanium dioxide. The flocculant used is one or more of starch, cellulose and chitosan.

[0058] The mass of the added flocculant accounts for 0.01%-0.05% of the mass of the slurry, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%. The crystallization temperature is 90-100°C, for example, 90°C, 95°C, 100°C, 105°C, 110°C, 120°C. The crystallization time is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h.

[0059] In the conversion of titanate into titanium dioxide, the volume of the organic acid solution added is 2-6 times the mass of the industrial deactivated denitration catalyst, wherein the mass of the industrial deactivated denitration catalyst is measured in g (grams) and the volume of the organic acid solution is measured in mL (milliliters).

[0060] In the conversion of titanate into titanium dioxide, the drying temperature is 50-100° C., for example, 50° C., 60° C., 70° C., 80° C., 90° C., 100° C. The drying time is 4-6 h, for example, 4 h, 4.5 h, 5 h, 5.5 h, 6 h.

[0061] The titanate is converted into titanium dioxide and calcined in a muffle furnace at a heating rate of 2-10°C / min to 500-900°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C. The calcination time is 4-6h, for example, 4h, 4.5h, 5h, 5.5h, 6h.

[0062] In addition, in the recovery method of the present invention, the centrifugal speed is 3000-5000 r / min, for example, 3000 r / min, 4000 r / min, 5000 r / min, in the three processes of efficient leaching of W and V, conversion of titanium dioxide into titanate, and conversion of titanate into titanium dioxide.

[0063] The present invention is applicable to the catalyst deactivated after industrial denitration reaction. Exemplarily, the main chemical components of the deactivated denitration catalyst are shown in Table 1.

[0064] Table 1 Main chemical components of deactivated denitrification catalyst

[0065]

[0066] The present invention adopts micro-liquid membrane technology to prepare high-purity titanium dioxide. The overall technical concept is: in an alkaline solution, under the joint action of a micro-liquid membrane reactor and a dispersant, the vanadium and tungsten components in the deactivated denitration catalyst are separated from the titanium component, and high-purity titanium slag is obtained by alkaline adjustment (the concentration of the second alkaline solution is greater than the concentration of the first alkaline solution). The obtained high-purity titanium slag is reacted with an organic acid, and the reaction process is divided into two stages of nucleation and crystallization through a micro-liquid membrane reactor, and with the assistance of a flocculant, a high-purity titanium dioxide product with a narrow particle size distribution and weak surface acidity is obtained through drying and roasting.

[0067] Compared with the prior art, the present invention has the following technical effects:

[0068] (1) The present invention adopts two steps to add alkaline solution. By controlling the mass concentration of the second alkaline solution to be greater than the mass concentration of the first alkaline solution, it is possible to achieve efficient leaching of W and V in the deactivated denitration catalyst during the efficient leaching of W and V, and convert part of the titanium dioxide in the deactivated denitration catalyst into titanate. In the process of converting titanium dioxide into titanate, the titanium in the deactivated denitration catalyst that has not been converted into titanate is converted into titanate, which makes the reaction more complete as a whole, thereby facilitating the removal of metals such as V and W, thereby improving the purity of titanium dioxide. And by selecting the mass concentration of the first alkaline solution to be 3wt%-10wt% and the mass concentration of the second alkaline solution to be 20wt%-40wt%, the degree of reaction is further improved, thereby improving the purity of titanium dioxide. Specifically, the purity of titanium dioxide recovered by the present invention is >99.2%.

[0069] (2) The present invention achieves better solid-liquid contact by adding a dispersant, thereby shortening the back-mixing time (i.e., the time for the vanadium and tungsten components in the deactivated denitration catalyst to separate from the titanium component), thereby improving the timeliness of recovery. Specifically, the back-mixing time of the present invention does not exceed 10 minutes, while the separation time of the prior art is 10-30 minutes. In addition, by adopting a method of adding high and low concentration alkaline solutions in two steps, the alkali washing time of high concentration alkali is greatly shortened (the alkali washing time of high concentration alkali of the present invention is only 2-5 hours, while the alkali washing time of the prior art is 8 hours), further improving the timeliness of recovery.

[0070] (3) The present invention proposes a high-purity titanium dioxide product and an efficient preparation method using a deactivated denitration catalyst as a raw material. The obtained titanium dioxide particles have a small particle size, with a maximum particle size of only 18.6-19.3 nm. The particle size distribution is narrow, with a D(30) particle size of less than 30 nm, a D(50) particle size of less than 40 nm, and a D(90) particle size of less than 50 nm. The total surface acid content is not less than 4.68×10 -4 mol / g (in line with the requirements of photocatalysts and denitration catalysts for the total acid content of titanium dioxide), titanium dioxide purity>99.2%. After the application of this technology, the recovery rate of titanium dioxide in the deactivated denitration catalyst is>98%, the component separation time in the alkaline solution does not exceed 10 minutes, and the nucleation time in the acid solution does not exceed 10 minutes. The titanium dioxide recovered from the deactivated catalyst can be used in the preparation of photocatalysts, electrocatalysts and denitration catalysts, and can achieve efficient decomposition of rhodamine and nitrogen oxides under mild conditions.

[0071] In a second aspect, the present invention also provides a high-purity titanium dioxide, which is recovered by the above-mentioned recovery process, has a small particle size, the most probable particle size is 18.6-19.3 nm; the particle size distribution is narrow, the D(30) particle size is less than 30 nm, the D(50) particle size is less than 40 nm, and the D(90) particle size is less than 50 nm; the total surface acid content is not less than 4.68×10 -4 mol / g (in line with the requirements of photocatalyst and denitration catalyst for the total acid content of titanium dioxide); titanium dioxide purity>99.2%.

[0072] In the third aspect, the present invention also provides an application of high-purity titanium dioxide recovered by the above-mentioned recovery process in the preparation of photocatalysts, electrocatalysts and denitration catalysts, which can achieve efficient decomposition of rhodamine and nitrogen oxides under mild conditions. Specifically, the high-purity titanium dioxide recovered by the deactivated denitration catalyst by the above-mentioned recovery process can be used as a catalyst directly as a photocatalyst to degrade rhodamine, and the degradation efficiency exceeds 90%, which is the first time to realize the application of functionalized regenerated titanium dioxide in deactivated denitration catalysts in photocatalysis. Alternatively, the high-purity titanium dioxide recovered by the above-mentioned recovery process of the deactivated denitration catalyst can be used as a carrier to prepare a denitration catalyst, and the denitration efficiency reaches 90%, realizing the closed-loop utilization of the deactivated denitration catalyst.

[0073] In a fourth aspect, the present invention also provides a method for preparing a titanium dioxide-based catalyst, comprising the following steps:

[0074] Step a: preparing an ammonium metavanadate solution;

[0075] Step b: adding the ammonium metavanadate solution to the titanium dioxide powder, stirring, drying, roasting and grinding to obtain V2O5-TiO2 particles;

[0076] Step c: preparing an aqueous solution of ammonium metatungstate;

[0077] Step d: adding an aqueous solution of ammonium metatungstate to the V2O5-TiO2 particles, stirring, drying, roasting, cooling, grinding and screening to obtain V2O5 / WO3-TiO2.

[0078] The titanium dioxide powder in step b is recovered from an industrial deactivated denitration catalyst.

[0079] Specifically, step a comprises: dissolving ammonium metavanadate in a co-solvent to obtain an ammonium metavanadate solution.

[0080] The co-solvent includes one or more of oxalic acid solution, monoethanolamine solution and diethanolamine solution.

[0081] In step a, the concentration of the prepared ammonium metavanadate solution is 0.4-0.6 mol / L.

[0082] In step b, the particle size of the titanium dioxide powder is 50-100 meshes. The mass volume ratio of the titanium dioxide powder to the ammonium metavanadate solution is: (0.3-0.5):1, wherein the mass of the titanium dioxide powder is in grams and the volume of the ammonium metavanadate solution is in mL.

[0083] In step b, the calcination temperature is 250-350° C., for example, 250° C., 280° C., 300° C., 330° C., 350° C. The calcination time is 2-4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours.

[0084] In step b and step d, the stirring speed is 2000-4000 r / min, and the stirring time is 10-20 minutes.

[0085] In step b and step d, the drying temperature is 90-130° C., for example, 90° C., 100° C., 110° C., 120° C., 130° C. The drying time is 10-20 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours.

[0086] Step c comprises: dissolving ammonium metatungstate in water to obtain an ammonium metatungstate aqueous solution, wherein the concentration of the prepared ammonium metatungstate aqueous solution is 0.2-0.3 g / mL.

[0087] In step d, the mass volume ratio of the V2O5-TiO2 particles and the ammonium metatungstate aqueous solution is: (1.5-2.5): 1, wherein the mass of the V2O5-TiO2 particles is measured in grams and the volume of the ammonium metatungstate aqueous solution is measured in mL.

[0088] In step d, the calcination temperature is 500-600° C., for example, 500° C., 520° C., 550° C., 580° C., 600° C. The calcination time is 2-4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours.

[0089] In step d, V2O5 / WO3-TiO2 particles with a particle size of 60-80 mesh are obtained by sieving.

[0090] The content and technical solutions of the present invention will be specifically and completely described below in conjunction with specific embodiments. However, it is obvious that the specific embodiments described further are only part of the content of the present invention, that is, they are not limited to the embodiments described herein.

[0091] Unless otherwise specified, the raw materials in the present invention can be obtained from commercial sources.

[0092] Example 1

[0093] Step 1: Weigh 50g of industrial deactivated denitration catalyst powder sieved to 50-100μm, mix it with 100mL of NaOH solution with a mass concentration of 10wt%, add dispersant (acrylate) to the mixed solution, and the volume of the dispersant accounts for 1‰ of the suspension. Pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.1mm, the temperature is 50℃, the suspension is back-mixed in the micro-liquid membrane reactor for 10min, centrifuged (3000r / min), and the supernatant is removed.

[0094] Step 2: Mix the solid obtained in the first step with 100 mL of 30 wt% concentrated NaOH solution, pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.1 mm, and the temperature to 50°C. Back-mix the suspension in the micro-liquid membrane reactor for 10 min, transfer it into the reactor, react for 4 h at 120°C and 0.3 MPa, and obtain the filter residue after centrifugation.

[0095] Step 3: Add 100 mL of organic acid (tartaric acid) solution to the residue obtained in the second step, pour into a micro-liquid membrane reactor at 50°C and 0.1 mm slit width for nucleation for 10 minutes, obtain slurry, add flocculant (starch), the mass accounting for 0.01% of the total, crystallize at 90°C for 5 hours, centrifuge and wash the obtained suspension, dry it in a 50°C oven for 6 hours, put it into a muffle furnace and heat it to 500°C at a heating rate of 2°C / min, and roast it for 6 hours. High-purity TiO2 products are obtained.

[0096] Example 2

[0097] Step 1: Weigh 50g of industrial deactivated denitration catalyst powder sieved to 50-100μm, mix it with 300mL of NaOH solution with a mass concentration of 5wt%, add dispersant (polyurethane) to the mixed solution, and the volume of the dispersant accounts for 5‰ of the suspension. Pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.5mm, the temperature is 100℃, the suspension is back-mixed in the micro-liquid membrane reactor for 5min, centrifuged (5000r / min), and the supernatant is removed.

[0098] Step 2: Mix the solid obtained in the first step with 300 mL of 20 wt% concentrated NaOH solution, pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.5 mm, and the temperature to 100 ° C. The suspension is back-mixed in the micro-liquid membrane reactor for 1 min, transferred to the reactor, reacted at 150 ° C, 2 MPa for 2 h, and centrifuged (5000 r / min) to obtain the filter residue.

[0099] Step 3: Add 200 mL of organic acid (citric acid) solution to the residue obtained in the second step, pour into a micro-liquid membrane reactor with a slit width of 100°C and 0.5 mm for nucleation for 1 minute, obtain a slurry, add a flocculant (cellulose) with a mass accounting for 0.05% of the total, crystallize at 120°C for 2 hours, centrifuge (5000r / min), wash with deionized water, dry in a 100°C oven for 4 hours, put into a muffle furnace and heat to 900°C at a heating rate of 10°C / min, and roast for 4 hours. A high-purity TiO2 product is obtained.

[0100] Example 3

[0101] Step 1: Weigh 50g of industrial deactivated denitration catalyst powder sieved to 50-100μm, mix it with 200mL of NaOH solution with a mass concentration of 8wt%, add dispersant (polyethylene glycol) to the mixed solution, and the volume of the dispersant accounts for 3%‰ of the suspension. Pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.2mm, the temperature is 80℃, the suspension is back-mixed in the micro-liquid membrane reactor for 8min, centrifuged (4000r / min), and the supernatant is removed.

[0102] Step 2: Mix the solid obtained in the first step with 200 mL of 25 wt% concentrated NaOH solution, pour the mixed suspension into the micro-liquid membrane reactor, adjust the slit of the micro-liquid membrane reactor to 0.1-0.5 mm, and the temperature to 80°C. Back-mix the suspension in the micro-liquid membrane reactor for 5 minutes, transfer it into the reactor, react for 3.5 hours at 125°C and 1 MPa, and obtain the filter residue after centrifugation (4000 r / min).

[0103] Step 3: Add 150mL of organic acid (citric acid and lauric acid) solution to the residue obtained in the second step, pour into a micro-liquid membrane reactor at 80°C and 0.2mm slit width for nucleation for 5min, add flocculants (cellulose and chitosan) to obtain slurry, the mass of which accounts for 0.03% of the total, crystallize at 105°C for 3.5h, centrifuge (4000r / min), wash with deionized water, dry in a 70°C oven for 5h, put into a muffle furnace and heat to 700°C at a heating rate of 6°C / min, and roast for 5h. High-purity TiO2 products are obtained.

[0104] Example 4

[0105] Step a: dissolving 0.13 g of ammonium metavanadate in 22 mL of oxalic acid solution (analytical grade) to obtain an ammonium metavanadate solution;

[0106] Step b: adding the ammonium metavanadate solution to 8.9 g of titanium dioxide powder recovered from an industrial deactivated denitration catalyst, stirring (3000 r / min, 15 minutes), drying (110° C., 12 hours), roasting (300° C., 3 hours), and grinding to obtain V2O5-TiO2 particles;

[0107] Step c: dissolving 1.04 g of ammonium metatungstate in 5 mL of water to obtain an ammonium metatungstate aqueous solution;

[0108] Step d: Add the aqueous solution of ammonium metatungstate to 9 grams of V2O5-TiO2 particles, stir, dry (110°C, 12 hours), roast (550°C, 3 hours), cool, grind and sieve to obtain V2O5 / WO3-TiO2.

[0109] Comparative Example 1

[0110] This comparative example is substantially the same as Example 3, except that the alkaline solution is not added in two steps, but is added in the first step, and no alkaline solution is added in the second step, and the concentration of the alkaline solution is 25 wt %.

[0111] Comparative Example 2

[0112] This comparative example is substantially the same as Example 3, except that the concentration of the first alkaline solution is 25 wt % and the concentration of the second alkaline solution is 8 wt %, that is, the concentration of the first alkaline solution is greater than that of the second alkaline solution.

[0113] Comparative Example 3

[0114] This comparative example is substantially the same as Example 3, except that hydrochloric acid is added in the third step instead of an organic acid.

[0115] Comparative Example 4

[0116] This comparative example is basically the same as Example 3, except that the mass concentration of the first alkaline solution is 15wt% (not within the range of 5wt%-10wt%), and the mass concentration of the second alkaline solution is 45wt% (not within the range of 20wt%-40wt%).

[0117] Comparative Example 5

[0118] This comparative example is substantially the same as comparative example 1, except that no micro-liquid membrane reactor is used, but back-mixing is performed in a flask and then transferred to a reactor for reaction for 8 hours.

[0119] Application Example 1

[0120] Rhodamine B was prepared into a solution of a certain concentration (5, 10, 15, 20 and 25 mg / L), and then the slurry prepared by TiO2 in Example 3 (250, 500, 750, 1 000 and 1 250 mg / L) was added, and the mixed solution of the reactants was stirred for 2 hours to reach the adsorption-desorption equilibrium level. All floating TiO2 particles were removed by a centrifuge, and the absorbance of the separated clarified reaction solution was measured by a UV-visible spectrophotometer, and the absorbance of Rhodamine B was measured at 554 nm. The degradation of Rhodamine B was observed. The results showed that the degradation efficiency of Rhodamine B exceeded 90%.

[0121] Application Example 2

[0122] Use oxalic acid solution as a co-solvent for ammonium metavanadate to obtain an ammonium metavanadate solution, add it to the TiO2 powder prepared in Example 3 and stir it thoroughly, dry it at 110°C for 12h after impregnation, and then place it in a muffle furnace and roast it at 300°C for 3h, take it out and grind it. Prepare an aqueous solution of ammonium metatungstate, use the same method to load the auxiliary agent WO3, and finally roast it at 550°C for 3h, grind and sieve it after cooling to obtain particles of 60 to 80 mesh, which are recorded as catalyst V2O5 / WO3-TiO2. The obtained catalyst is applied to the selective catalytic reduction denitration process. The results show that the denitration efficiency is 90%.

[0123] Some properties of the titanium dioxide obtained in Examples 1-3 and Comparative Examples 1-3 were tested under the same test conditions. The results are shown in Table 2.

[0124] Table 2 Some properties of titanium dioxide

[0125]

[0126]

[0127] It can be seen from Table 2 that the most probable particle size of the titanium dioxide obtained in Examples 1-3 of the present invention is 18.6-19.3 nm, which proves that the particle size of the titanium dioxide prepared by the method of the present invention is small. It can be seen from the particle size distribution data in Table 2 that the particle size distribution of the titanium dioxide prepared by the method of the present invention is narrow, with a D(30) particle size of less than 30 nm, a D(50) particle size of less than 40 nm, and a D(90) particle size of less than 50 nm. And the total surface acid content is not less than 4.68×10 -4 mol / g (in line with the requirements of photocatalyst and denitration catalyst for the total acid content of titanium dioxide), the purity of titanium dioxide is 99.2%-99.6%, both greater than 99.2%. After applying the technology of the present invention, the recovery rate of titanium dioxide in the deactivated denitration catalyst is 98.7%-99.3%, both greater than 98%.

[0128] It can also be seen from Table 2 that when the alkaline solution is not added in two steps (Comparative Example 1), the purity of titanium dioxide is only 94.5%, which is significantly lower than the greater than 99.2% of the present invention. In addition, when the concentration of the first alkaline solution is greater than the concentration of the second alkaline solution (Comparative Example 2), the purity of titanium dioxide is only 95%, which is also significantly lower than the greater than 99.2% of the present invention. When hydrochloric acid is not added in the third step (Comparative Example 3), the total surface acidity of titanium dioxide is 6.72×10 -4 mol / g, significantly higher than the 4.68×10 -4 mol / g, indicating that the acidity of the titanium dioxide recovered when hydrochloric acid is stronger than that of the titanium dioxide recovered when organic acid is used. In addition, when the micro-liquid membrane reactor is not used and the alkaline solution is not added in two steps, a longer reaction time (alkali washing time of 8 hours, much longer than the 2-5 hours of the present invention) (Comparative Example 5) is used, the most probable particle size of the titanium dioxide obtained is 24.2nm, much higher than the 18.6-19.3nm of the present invention, and the particle size distribution is 0-80nm, which is obviously wider than the particle size distribution of the present invention, that is, the micro-liquid membrane reactor is not used, and the alkaline solution is not added in two steps, even if a longer reaction time is used, the performance of the titanium dioxide obtained is much lower than that of the present invention.

[0129] In addition, the present invention also tested and characterized the titanium dioxide obtained in Examples 1-3, and the results are shown in Figure 1 and Figure 2. The specific test and characterization conditions are as follows:

[0130] A Shimadzu XRD-600 X-ray powder diffractometer (λ=0.15406nm) was used to characterize and analyze the crystal structure of the catalyst material. The analytical instrument is equipped with a Cu target and the ray type is Kα ray. Take an appropriate amount of powder catalyst and place it in the groove of the rectangular glass sheet used for the test. Use a pressing plate to flatten the surface of the catalyst and place it on the test table of the instrument. The scanning range is 2θ=10~80℃, the scanning speed is 1deg / min, and the instrument error range is ±0.04℃. Under this condition, the sample is subjected to X-ray diffraction, and the X-ray diffraction spectrum (XRD) is obtained. See Figure 1 .

[0131] The morphology of the formed catalyst was characterized by a scanning electron microscope (SEM, Zeiss Supra 55). The catalyst was dispersed in ethanol, ultrasonicated for 15 minutes, and then dropped on a silicon wafer for scanning testing. The particle size was then statistically analyzed using Nanomeasurer software.

[0132] Depend on Figure 1It can be seen that only the diffraction peak of anatase TiO2 was observed in the XRD spectrum of the final sample, indicating that the sample has high purity, that is, TiO2 is well extracted and separated under high concentration alkali solution and organic acid that is weaker than inorganic acid.

[0133] As can be seen from FIG. 2( a ), the sample particles in the embodiment of the present invention are approximately elliptical in shape, with a smooth surface and a relatively concentrated particle distribution (see FIG. 3( a )).

[0134] As can be seen from Figure 2(b), although most of the sample particles of Comparative Example 5 are also elliptical, they contain obvious flaky structures, which means that the sample contains Na ions that are not fully washed, the purity of the sample TiO2 is low, and the metatitanic acid is not completely converted, which is not conducive to the subsequent catalyst synthesis and utilization. And when the alkali washing time is shortened by half (the alkali washing time of Example 1 is 4h, and the alkali washing time of Comparative Example 5 is 8h), the particle size and particle size distribution of the sample of the embodiment of the present invention are significantly lower than those of the comparative example (see Figure 3(b)), which is conducive to the subsequent synthesis of titanium dioxide-based catalysts.

[0135] It should be noted that when the dispersant, organic acid solution, and flocculant are replaced with other substances listed above except for Examples 1-3, or the amount of the substance and the process conditions are replaced with the amount or process conditions listed above except for Examples 1-3, the performance of the titanium dioxide obtained is similar to that of Examples 1-3, and they are not listed one by one here.

[0136] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for improving the recovery rate of titanium dioxide, characterized in that: The following steps are involved: Efficient leaching of W and V: Mix the industrial deactivated denitrification catalyst with an alkaline solution, react, remove the supernatant, and obtain a solid; Titanium dioxide is converted into titanate: the obtained solid is mixed with an alkaline solution, reacted, and a filter residue is obtained; Titanate is converted into titanium dioxide: an organic acid solution is added to the obtained filter residue to obtain a solid-liquid mixture, the solid-liquid mixture is transferred into a reactor for nucleation to obtain a slurry, a flocculant is added to the slurry for crystallization to obtain a suspension, and the suspension is separated and calcined to obtain TiO2.

2. The method according to claim 1, characterized in that The flocculant includes one or more of starch, cellulose and chitosan.

3. The method according to claim 2, characterized in that The mass of the flocculant accounts for 0.01%-0.05% of the mass of the slurry.

4. The method according to claim 1, characterized in that: The organic acid solution is one or more mixed acids selected from tartaric acid, citric acid, lauric acid and oxalic acid.

5. The method according to claim 4, characterized in that The concentration of the organic acid solution is 0.5-2 mol / L.

6. The method according to claim 1, characterized in that The crystallization temperature is 90-100°C and the crystallization time is 2-5h.

7. The method according to claim 1, characterized in that The calcination temperature is 500-900°C and the calcination time is 4-6h.

8. The method according to claim 1, characterized in that The recovery rate of TiO2 is greater than 98%.

9. A titanium dioxide, characterized in that: The titanium dioxide is recovered by the method according to any one of claims 1 to 9, wherein the particle size of the titanium dioxide is small, the most probable particle size is 18.6-19.3 nm; the particle size distribution is narrow, the D(30) particle size is less than 30 nm, the D(50) particle size is less than 40 nm, and the D(90) particle size is less than 50 nm; the total surface acid content is not less than 4.68×10 -4 mol / g; purity>99.2%.

10. Use of the titanium dioxide according to claim 9 in the preparation of photocatalysts, electrocatalysts and denitrification catalysts.